Pain Beyond Biology: An Empirical Study of the Mind Body Soul Connection in Chronic Pain Experience in School - Ricci, Matteo (BIRCU, 2012)
Chronic pain is one of the most prevalent and challenging health conditions worldwide, affecting millions of individuals and significantly reducing quality of life. Traditional biomedical models have long conceptualized pain as a purely physiological response to tissue damage; however, growing evidence suggests that pain is a multidimensional experience shaped by psychological, social, and spiritual factors. This study investigates the relationship between biological, psychological, and spiritual dimensions in the lived experiences of individuals with chronic pain. Using a mixed-methods research design, the study combines quantitative surveys with qualitative interviews to explore how emotional states, cognitive beliefs, and spiritual practices influence pain perception and coping mechanisms. Data were collected from 120 participants experiencing chronic pain across multiple clinical and community settings. Quantitative results indicate significant correlations between psychological distress, spiritual wellbeing, and reported pain intensity. Participants who reported higher levels of spiritual coping and meaning-making demonstrated lower perceived pain severity and greater resilience. Qualitative findings further reveal that patients frequently interpret pain within broader narratives of identity, purpose, and spiritual growth. These findings support the biopsychosocial-spiritual model of health and highlight the importance of integrative approaches to pain management. The study concludes that effective pain treatment requires healthcare systems to address emotional, cognitive, social, and spiritual dimensions alongside biological factors.